Pengaruh model pembelajaran RCCDE terhadap hasil belajar siswa kelas VII MTs Miftahul Ulum Sumber Baru - Ibni Nimun, Syaifullah; Hikamah, Siti Roudlotul; Hakim, Miftahul (Universitas Islam Jember, 2021)
Research on student learning outcomes of class VII MTs. Miftahul Ulum Karang Bayat Sumber Baru for the 2019/2020 school year with 42 respondents from 125 students who were taken by stratified random sampling. The method used in this study is a test method with a Quasi Experimental Design.Students who are used as subjects in the research sample, have the same ability, because b Reading Concept Map Connection Discussion Evaluation oth classes get the same science material. The experimental class uses the Reading Concept Map Connection Discussion Evaluation (RCCDE) learning model and the control class uses the conventional method. It is known from the results of data analysis calculations that the use of the Reading Concept Map Connection Discussion Evaluation (RCCDE) learning model can affect learning outcomes, this is evidenced by the results of the ANOVA test scores which obtain Sig 0.000 < 0.05 (0.050). From the analysis of the data above, it is continued with the paired samples test. the results of the calculation of this analysis obtained a value of Sig (2-tailed) of 0.000 <0.05, it can be concluded that there is a difference in student learning outcomes between the pre-test of the experimental class and the post-test of the experimental class. Keywords : RCCDE Model, Learning Outcomes, Air Pollution